2012
DOI: 10.1007/s12257-012-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of epigallocatechin gallate and its glucoside on the human intestinal maltase inhibition

Abstract: Human intestinal maltase (HMA) is an αglucosidase responsible for the hydrolysis of α-1,4-linkages from the non-reducing end of malto-oligosaccharides. HMA has become an important target in the treatment of type-2 diabetes. In this study, epigallocatechin gallate (EGCG) and EGCG glucoside (EGCG-G1) were identified as inhibitors of HMA by an in vitro assay with IC 50 of 20 ± 1.0 and 31.5 ± 1.0 µM, respectively. A Lineweaver-Burk plot confirmed that EGCG and EGCG-G1 were competitive inhibitors of maltose substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…These data show that the ligand binds in a region of the protein mainly composed by aromatic and hydrophilic side chains, forming a combination of hydrophobic interactions and hydrogen bonds that favored the binding. Different types of interactions have been reported for EGCG with other proteins such as human salivary α-amylase, 48 human intestinal maltase, 49 and amyloid-β, 50 which shows that EGCG binding for each system has a different nature. Among the preferred docking poses, Y37, Y50, and Q92 repeatedly play an important role interacting with the ligand.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These data show that the ligand binds in a region of the protein mainly composed by aromatic and hydrophilic side chains, forming a combination of hydrophobic interactions and hydrogen bonds that favored the binding. Different types of interactions have been reported for EGCG with other proteins such as human salivary α-amylase, 48 human intestinal maltase, 49 and amyloid-β, 50 which shows that EGCG binding for each system has a different nature. Among the preferred docking poses, Y37, Y50, and Q92 repeatedly play an important role interacting with the ligand.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our previous results indicated that B2-3’- O -gallate ( K i = 0.30 ± 0.03 μM, K i’ = 1.42 ± 0.01 μM), ECG ( K i = 0.21 ± 0.04 μM, K i’ = 2.34 ± 0.06 μM), and quercetin ( K i = 1.44 ± 0.04 μM, K i’ = 9.33 ± 0.10 μM) were mixed-competitive inhibitors of α-glucosidase [15]. Furthermore, a Lineweaver–Burk plot indicated that epigallocatechin gallate was a competitive inhibitor against maltose substrate for maltase, and the K i calculated from a Dixon plot was 5.93 ± 0.26 µM [25].…”
Section: Resultsmentioning
confidence: 99%
“…The three-dimensional coordinates in the X-ray crystal structure of NS3 pro (PDB accession number 2VBC) [27] obtained from the Protein Data Bank [26,31] were used as the receptor model for the structural-based VS docking simulations. The NS3 pro docking library comprised 300,000 compounds from ChemDiv Inc. (San Diego, CA, USA), a commercially available compound library, was used for VS. AutoDock version 3.0.5 was used for the computational molecular docking simulation of flexible small molecules to rigid proteins using ligand and rigid proteins [32,33]. Large-scale computations were conducted between 2VBC and 300,000 compounds using the GVSS [26].…”
Section: Methodsmentioning
confidence: 99%